Relationship Between Diabetes Distress and Self Management on Type 2 Diabetes Mellitus Patients in Sumbang District Banyumas - Fadillah, Aulia Nur; Wulansari, Rahmawati; Kuncoro, Prasetyo Tri; Isnaya, Purwa Riana; Oktavilia, Ernasiwi Astri; Anamani, Teguh (Medical and Health Journal, 2025)
Background: Diabetes distress is a form of anxiety, worry, fear, and perceived threat related to the struggles experienced by individuals living with diabetes mellitus. The presence of diabetes distress is associated with reduced self-care (self-management). Diabetes mellitus self-management refers to a series of actions taken by individuals to manage their medical condition, including dietary regulation, physical activity management, regular and consistent intake of diabetes medication, blood glucose monitoring, and routine foot care. Objective: This study aims to determine the relationship between diabetes distress and self- management in patients with type 2 diabetes mellitus in Sumbang District, Banyumas. Method: This research uses an analytical observational study with a cross sectional approach. The sampling technique used was a total sampling of 55 people. Data analysis using the chi-square test. Research Results: The results of the research showed that self-management of type 2 DM patients was mostly in the sufficient category, namely 25 people (45.5%) and diabetes distress of type 2 DM patients is in the mild category, namely 35 people (63.6%). There is a relationship between diabetes distress and self-management in type 2 diabetes mellitus patients in Sumbang District, Banyumas (p = 0.000). Conclusion: Diabetes distress is related to self-management in type 2 diabetes mellitus patients.